2021
DOI: 10.3390/curroncol29010012
|View full text |Cite
|
Sign up to set email alerts
|

Sâkipakâwin: Assessing Indigenous Cancer Supports in Saskatchewan Using a Strength-Based Approach

Abstract: Given that the health care system for Indigenous people tends to be complex, fragmented, and multi-jurisdictional, their cancer experiences may be especially difficult. This needs assessment study examined system-level barriers and community strengths regarding cancer care experiences of Indigenous people in Saskatchewan. Guided by an advisory committee including Indigenous patient and family partners, we conducted key informant interviews with senior Saskatchewan health care administrators and Indigenous lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The findings from this study are largely in line with other published literature across different Indigenous groups (Adcock et al, 2019; Butler et al, 2020; Dodd et al, 2021; Kolahdooz et al, 2014; Maar et al, 2013, 2016; Manderson & Hoban, 2006; Nugus et al, 2018; Whop et al, 2021; Witham et al, 2021). Namely, a common theme that arises across studies is the importance of providing culturally competent care when it comes to cervical cancer screening (Adcock et al, 2019; Butler et al, 2020; Kolahdooz et al, 2014; Witham et al, 2021). This need holds true for other healthcare services as well, as shown in a study exploring traumatic brain injury among women survivors of intimate partner violence within Indigenous populations in Canada, which discusses challenges around the need for culturally safe healthcare practices within Inuit communities (Haag et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings from this study are largely in line with other published literature across different Indigenous groups (Adcock et al, 2019; Butler et al, 2020; Dodd et al, 2021; Kolahdooz et al, 2014; Maar et al, 2013, 2016; Manderson & Hoban, 2006; Nugus et al, 2018; Whop et al, 2021; Witham et al, 2021). Namely, a common theme that arises across studies is the importance of providing culturally competent care when it comes to cervical cancer screening (Adcock et al, 2019; Butler et al, 2020; Kolahdooz et al, 2014; Witham et al, 2021). This need holds true for other healthcare services as well, as shown in a study exploring traumatic brain injury among women survivors of intimate partner violence within Indigenous populations in Canada, which discusses challenges around the need for culturally safe healthcare practices within Inuit communities (Haag et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The findings from this study are largely in line with other published literature across different Indigenous groups (Adcock et al, 2019; Butler et al, 2020; Dodd et al, 2021; Kolahdooz et al, 2014; Maar et al, 2013, 2016; Manderson & Hoban, 2006; Nugus et al, 2018; Whop et al, 2021; Witham et al, 2021). Namely, a common theme that arises across studies is the importance of providing culturally competent care when it comes to cervical cancer screening (Adcock et al, 2019; Butler et al, 2020; Kolahdooz et al, 2014; Witham et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The support systems for Indigenous cancer survivors are well documented in qualitative research, and the important role of the family is evident ( Carr et al, 2020 ; Gifford et al, 2019 ; Roberts et al, 2020 ). In Witham and colleagues’ study, Indigenous patients, survivors, and family members highlighted the value of kinship ( Witham et al, 2022 ). The authors identified that family could play an important role in providing support for those who need to travel to attend medical appointments by hosting family members and attending appointments with them ( Witham et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A knowledge synthesis on trust and worldview in shared decision-making with Indigenous patients revealed that historical trauma, lack of system support, and lack of reciprocal respect contributed to a decreased trust in healthcare providers ( Groot et al, 2020 ). A needs assessment study, entitled Sâkipakâwin, explored the barriers to cancer support for First Nations and Métis people in Saskatchewan and highlighted the need for better support for Indigenous cancer survivors ( Witham et al, 2022 ).…”
Section: Background and Purposementioning
confidence: 99%